2022
DOI: 10.1155/2022/8414135
|View full text |Cite|
|
Sign up to set email alerts
|

Rehabilitation of Sepsis Patients with Acute Kidney Injury Based on Intelligent Medical Big Data

Abstract: The objective of this study was to explore rehabilitation of patients with acute kidney injury (AKI) treated with Xuebijing injection by using intelligent medical big data analysis system. Based on Hadoop distributed processing technology, this study designed a medical big data analysis system and tested its performance. Then, this analysis system was used to systematically analyze rehabilitation of sepsis patients with AKI treated with Xuebijing injection. It is found that the computing time of this system do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…And through direct interaction with electronic medical records, they broadened the way to use big data and provided the right dose for each patient at the right expounded the importance of big data to explore clinical trials systematically and, respectively. In the exploration of big data in the past 2 years, a number of studies have carried out analysis of individualized computational models constructed through big data, pointing out risk factors for high mortality in patients with critical symptoms (31)(32)(33). Finally, in terms of the relationship between clinical drug R&D and big data, we have not seen any evidence that relevant big data is used in drug R&D in the field of critical care medicine.…”
Section: Background and Evidencementioning
confidence: 87%
See 1 more Smart Citation
“…And through direct interaction with electronic medical records, they broadened the way to use big data and provided the right dose for each patient at the right expounded the importance of big data to explore clinical trials systematically and, respectively. In the exploration of big data in the past 2 years, a number of studies have carried out analysis of individualized computational models constructed through big data, pointing out risk factors for high mortality in patients with critical symptoms (31)(32)(33). Finally, in terms of the relationship between clinical drug R&D and big data, we have not seen any evidence that relevant big data is used in drug R&D in the field of critical care medicine.…”
Section: Background and Evidencementioning
confidence: 87%
“…The application carrier should be effectively integrated with the hospital information system, which can obtain high-dimensional information in real time, and be equipped with a prediction model. Based on Hadoop distributed processing technology, Xia et al ( 33 ) designed a big data analysis system for intensive care medicine, and conducted a performance test through the “Study on the Effect of Xuebijing on AKI-related Sepsis” ( 33 ). The information system of intensive care big data can integrate ICU high-dimensional information, obtain analysis data in real time, and use it as a carrier for results of intensive care big data such as prediction models and scores ( 151 ).…”
Section: Consensus Textmentioning
confidence: 99%
“…A retrospective case series showed that a four-drug combination of Huashi Baidu granules with Xiyanping, Xuebijing, and Shenmai injections was effective for SARS-CoV-2 RNA clearance, promoted lung lesion opacity, and reduced inflammation in severe patients with severe COVID-19 [42] . A clinical study of 640 patients demonstrated that XBJ can improve the renal function of patients with sepsis and kidney injury; its therapeutic effect was considerably stronger than that of Western medicine, demonstrating clinical application value [43] .…”
Section: Clinical Studies Of Tmtfs In the Treatment Of Severe-tocriti...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%